Sanitarian conditions and care in the Paraguayan war - Pedro Ruiz B Nassar; Fernando Rocha Porto; Simone Aguiar; Juliane Aguiar da Rocha; Anna Paula Ataide (Universidad de Alicante, 2016)
Objective: To analytically identify, in the periodical El Centinela, news related to the sanitary conditions and care towards the wounded in the Paraguay war. Method: Serial history approach three news fragments were used to illustrate the sanitary conditions and care towards the wounded. Results: The hostile sanitary conditions where the practice of care, compress with rips of skirts of women to stop the bleeding and the use of medicinal and nutritional marijuana were one of the methods used for care. Conclusion: There wasn't the pretense of deepen the sanitary conditions and care to injured in action but carried that El Centinela periodical has regular daily richness of war, which allows somehow reassemble, even minimally, the history of care.